Impact of Consolidative Unrelated Cord Blood Transplantation on Clinical Outcomes of Patients With Relapsed/Refractory Acute B Lymphoblastic Leukemia Entering Remission Following CD19 Chimeric Antigen Receptor T Cells - Xu, Qianwen; Xue, Lei; An, Furun; Xu, Hui; Wang, Li; Geng, Liangquan; Zhang, Xuhan; Song, Kaidi; Yao, Wen; Wan, Xiang; Tong, Juan; Liu, Huilan; et al. (Frontiers in Immunology, 2022)
Background While chimeric antigen receptor (CAR)-T cell therapy is becoming widely used in hematological malignancies with remarkable remission rate, their high recurrence remains an obstacle to overcome. The role of consolidative transplantation following CAR-T cell-mediated remission remains controversial. We conducted a retrospective study to explore whether bridging to unrelated cord blood transplantation (UCBT) could improve the prognosis of patients entering remission after CAR-T therapy with different characteristics through subgroup analyses. Methods We reviewed 53 patients with relapsed/refractory (R/R) B-cell acute lymphoblastic leukemia (B-ALL) successfully infused with CD19 CAR-T cells and achieved complete remission (CR). In this study, 25 patients received consolidative UCBT (UCBT group) and 28 patients did not accept any intervention until relapse (non-UCBT group). Subgroup analysis on prognosis was then performed according to gender, age, number of previous relapses, tumor burden, presence of poor prognostic markers, and structure of CAR. Results Compared with the non-UCBT group, patients who underwent consolidative UCBT had better median event-free survival (EFS; 12.3 months vs. 6.2 months; P = 0.035) and relapse-free survival (RFS; 22.3 months vs. 7.2 months; P = 0.046), while no significant difference was found in overall survival (OS; 30.8 months vs. 15.3 months; P = 0.118). Subsequent multivariate analysis revealed that bridging to UCBT was a protective factor for RFS (P = 0.048) but had no significant effect on EFS (P = 0.205) or OS (P = 0.541). In the subgroup analysis, UCBT has an added benefit in patients with specific characteristics. Patients who experienced ≥2 relapses or with sustained non-remission (NR) showed better RFS (P = 0.025) after UCBT. Better EFS was seen in patients with poor prognostic markers (P = 0.027). In the subgroup with pre-infusion minimal residual disease (MRD) ≥5% or with extramedullary disease (EMD), UCBT significantly prolonged EFS (P = 0.009), RFS (P = 0.017), and OS (P = 0.026). Patients with occurrence of acute graft-versus-host disease (aGVHD) appeared to have a longer duration of remission (P = 0.007). Conclusion Consolidative UCBT can, to some extent, improve clinical outcomes of patients with R/R B-ALL entering remission following CD19 CAR-T therapy, especially in patients with more recurrences before treatment, patients with poor prognostic markers, and patients with a higher tumor burden. The occurrence of aGVHD after UCBT was associated with better RFS.